2017
DOI: 10.1007/s00167-017-4507-9
|View full text |Cite
|
Sign up to set email alerts
|

No impact of under-correction and joint line obliquity on clinical outcomes of total knee arthroplasty for the varus knee

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 36 publications
4
37
2
Order By: Relevance
“…The HKA was defined as the angle between the mechanical axes of the femur and tibia. A HKA greater than or equal to 3° was defined as varus knee deformity [13]. The TTA was defined as the angle between the tibia anatomical axis and talus upper surface.…”
Section: Methodsmentioning
confidence: 99%
“…The HKA was defined as the angle between the mechanical axes of the femur and tibia. A HKA greater than or equal to 3° was defined as varus knee deformity [13]. The TTA was defined as the angle between the tibia anatomical axis and talus upper surface.…”
Section: Methodsmentioning
confidence: 99%
“…Rassir et al [22] and William et al [36] discovered that the alignment had a large influence on PROMS postoperatively. While Slevin et al [26] and Rames et al [27] did not investigate the same results. In our research, no correlations were found between the alignment of components at 1 week after surgery and PROMS at 2 years after surgery, which is consistent with the latter results (Table S3).…”
Section: Discussionmentioning
confidence: 86%
“…This, to some extent, reminds doctors to avoid medial over-hang of the tibial component, even if over-hang is inevitable during surgery. The relationship between the alignment and the PROMS after surgery remains unclear [7,[22][23][24][25][26][27]36]. Rassir et al [22] and William et al [36] discovered that the alignment had a large influence on PROMS postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies 14,15 showed inconsistent results, a retrospective study was conducted to better identify the association between mechanical alignment and post-operative HSS score after primary TKA in this study. The most important finding of the current study was that we found no significant association between post-operative lower limb mechanical alignment and HSS score for patients in Chinese with pre-operative constitutional varus knee caused by combined deformities.…”
Section: Discussionmentioning
confidence: 98%